2007
DOI: 10.1016/j.steroids.2006.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Gβγ signaling reduces intracellular cAMP to promote meiotic progression in mouse oocytes

Abstract: In nearly every vertebrate species, elevated intracellular cAMP maintains oocytes in prophase I of meiosis. Prior to ovulation, gonadotropins trigger various intra-ovarian processes, including the breakdown of gap junctions, the activation of EGF receptors, and the secretion of steroids. These events in turn decrease intracellular cAMP levels in select oocytes to allow meiotic progression, or maturation, to resume. Studies suggest that cAMP levels are kept elevated in resting oocytes by constitutive G protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
(46 reference statements)
1
8
0
Order By: Relevance
“…This study further hypothesized that LH may activate PDEs by lowering cGMP or by phosphorylating PDEs in the oocyte thereby decreasing cAMP levels (100). A more recent study, also in mouse oocyte, has reported that unlike Xenopus, the G-signaling decreases cAMP levels and can induce meiosis (158). The G-induced decrease in cAMP levels does not involve a constitutive G-signaling but rather is mediated by partially inhibiting the Gs-stimulated rise in cAMP levels.…”
Section: Role Of G-proteins In Decreasing Camp Levels In the Oocyte Fmentioning
confidence: 70%
“…This study further hypothesized that LH may activate PDEs by lowering cGMP or by phosphorylating PDEs in the oocyte thereby decreasing cAMP levels (100). A more recent study, also in mouse oocyte, has reported that unlike Xenopus, the G-signaling decreases cAMP levels and can induce meiosis (158). The G-induced decrease in cAMP levels does not involve a constitutive G-signaling but rather is mediated by partially inhibiting the Gs-stimulated rise in cAMP levels.…”
Section: Role Of G-proteins In Decreasing Camp Levels In the Oocyte Fmentioning
confidence: 70%
“…As mentioned, an unusual feature of Xenopus oocytes is that G␤␥ and G␣ s appear to signal together to stimulate adenylyl cyclase, elevate intracellular cAMP, and hold oocytes in meiotic arrest (4,(6)(7)(8). This differs from mouse oocytes, in which G␤␥ signaling may, in fact, inhibit adenylyl cyclase and promote oocyte maturation (20). The difference between these species is likely due to the presence of adenylyl cyclase VII in Xenopus (7, 21), but not mouse, oocytes.…”
Section: Fig 5 Collagenase Cleaved Cell Surface Gpr3 and Enhanced Tmentioning
confidence: 99%
“…Second, the AR interacts with caveolin 1 and is localized primarily in lipid rafts within the membrane [74]. Third, androgen activation mediates rapid G protein signaling via the membrane-localized AR [75][76][77][78]. Finally, androgen activation of membrane-localized AR leads to rapid transactivation of the EGF receptor via a MMP-mediated release of EGF receptor ligands, after which both Akt and MAPK pathways are activated, the latter of which is important for subsequent nuclear AR-mediated signaling [79][80][81][82][83] (Fig.…”
Section: Androgenmentioning
confidence: 99%